Scooby-Doo! and Kiss : rock and roll mystery : original movie [videorecording (DVD)] - Kreig, Jim; Shinick, Kevin, 1969- ([Publisher not identified], 2015)
When a ghoul begins to terrorize an amusement park, the Mystery Inc. gang comes face to face with the legendary rock group KISS, who claim they're also there to solve the mystery. Now the two groups must learn to work together as the clues lead them on a cosmic journey to another dimension.